Semantic and Cultural features of love declaration in English and Vietnamese folklores / Hoàng Thị Thủy - Hoàng, Thị Thủy
Love expressions have been one of the most fascinating topics that attracts a large number of people. In English and Vietnamese, the way people choose to express love is not the same as it is affected by cultural values. This research investigates how English and Vietnamese speakers express their love declarations in in terms of semantic and cultural features. In addition, the researcher tries to explore the similarities and differences in semantic and cultural features between English and Vietnamese folklores. Besides, the thesis also attempts to explain what are behind the differences uncovered in the investigation. The study suggests how learners and users can use Love declaration in both languages. Furthermore, the thesis gives some theoretical background in which the concepts of semantics, features of culture, definitions of folklores, Love declaration, semantic and cultural characteristics of Love declarations in both English and Vietnamese are mentioned. A large number of methods are conducted, such as descriptive, contrastive, synthetic and analytic methods. However, the study mainly focuses on analysis and comparison of Love declaration in English and Vietnamese folklores. What is more, a variety of English and Vietnamese folklores about Love declaration from books, previous studies, Internet, ect have been collected to make the corpus of the study. In order to make the thesis more convincing when showing the similarities and differences of Love declaration in the two languages, some examples are taken in two both languages into consideration. Finally, the findings are discovered. The results show some characteristics of English and Vietnamese love declarations in folklores in terms of semantics and culture.